(untitled) (Revista de Crítica Literaria Latinoamericana, 2010)
This study examines the adaptation of prophetic elements in the narrative of the Brazilian Jewish author Samuel Rawet (1929-1984), by means of a textual analysis of the links between four narratives by this author and prophetic and apocalyptic literature, represented, not only by the prophetic books of the Hebrew Bible and the Christian Apocalypse, but in a variety of works. Rawet utilizes certain canonical conventions such as supernatural messengers, demons, and the concepts of curse and redemption, but transforming them radically to produce fundamentally secular narratives focused on neoprophetic protagonists.